Reorientation of Indonesia's Foreign Policy In President Jokowi's Era: Case Studies Southwest Pacific - Laode Muhamad Fathun (Universitas Diponegoro, 2024)
Looking at the contribution of Indonesia's leadership in the region that has been built for a long time, it can be seen, among others, through Indonesia's prominent role in the Southwest Pacific region through the Southwest Pacific Dialogue (SwPd). Seeing how Indonesia became the initiator at that time can be the basis for Indonesia's leadership in the Southwest Pacific region today. This paper aims to find out how Indonesia's geopolitically oriented foreign policy under the leadership of President Jokowi is further examined in the southwest Pacific region. The theory used in this study is poliheuristic theory. The research method used is a qualitative paradigm with descriptive analysis and secondary data collection techniques from various relevant references. The results show that under President Jokowi's leadership, a reorientation of Indonesia's foreign policy in the Southwest Pacific region is crucial. This is based on the orientation of Indonesia's national interests, especially securing and ensuring that the political and security fields become the top priorities in foreign policy.